PENGARUH STRATEGI PEMBELAJARAN TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN SISWA KELAS V YANG MEMILIKI KECERDASAN EMOSIONAL DAN GAYA BELAJAR YANG BERBEDA DI KECAMATAN RENDANG, KARANGASEM, BALI: instructional strategy, emotional intelligence, learning style, learning achievement - I Wayan Arsana (Universitas PGRI Adi Buana, 2011)
Teaching paradigm followed by teachers is reflected on their teaching strategy used. The teaching strategy is the way that containts the steps or procedures which are used in certain condition to reach the desired learning result achievement. One of teaching strategies that needs to be tested for the effectiveness is called teaching strategy of Cooperative STAD (Student Teams-Achievement Divisions). The essence is the learners work in heterogeneous groups that emphasize more cooperative process in their heterogeneous group either in their capability, sexes, races and so on, and evaluation can be done by individual or group assessment. To know the effectiveness of teaching cooperative STAD in teaching Civics Education to the fifth grade of elementary school, as comparation, the Expository teaching strategy is used, this strategy is very commonly used by teachers. The aim of this research is to ditermine to test the influence of teaching strategy (cooperative STAD and expository), emotional intelligence and learning style toward learning result of Civics Education (PKn). This toward research is quasi experimental research using factorial design of nonequivalent control group design. The data then was processed by using inferencial statistic with analytic technique of factorial varian (anava) 2 x 2 x 2. The calculation result of descriptive statistic indicated the aplication of teaching strategy of Cooperative STAD mean 65,32 gave better influence on the learning result than the application of Expository teaching strategy mean 56,79.